Problematika Sertipikasi Hak Atas Tanah Melalui Pendaftaran Tanah Sistematis Lengkap di Kantor Pertanahan Kabupaten Kutai Barat - Selli Andriani; Andri Pranata (Wadah Inovasi Indonesia, 2024)
This study examines the issues surrounding land rights certification through the Complete Systematic Land Registration (PTSL) program at the West Kutai Regency Land Office. The research aims to identify the challenges faced in the certification process and the role of the land office in addressing these issues. Utilizing a normative legal research method, data was collected through literature studies and field research. The findings reveal several problems, including unstable internet connections, unvalidated National Identity Numbers (NIK), incomplete documentation, low public understanding of the importance of certificates, geographical challenges, and inadequate human resources. The study also highlights the proactive measures taken by the West Kutai Land Office, such as implementing Starlink for internet connectivity, coordinating with Dukcapil for data validation, conducting massive socialization efforts, and hiring additional staff to improve service delivery.